EVALUATION OF GUIDANCE AND COUNSELING IN STUFFLBEAM AND DAHIR STONE PERSPECTIVE - Irvan Budhi Handaka; Irfan Fahriza; Nadia Aulia Nadhirah; Kawai Norimune (Universitas Pendidikan Indonesia, 2023)
This article aims to comprehensively describe the evaluation of guidance and counseling in the perspective of Stuffelbeam and Dahir Stone. This research method uses the literature study method. The data obtained were compiled, analyzed, and concluded so as to obtain conclusions regarding the study of literature. The stages in the literature review are 1) planning, 2) conducting, 3) reporting. The data of the study that was carried out included a study of understanding, philosophical foundations and evaluation principles based on the perspective of Stuffelbeam and Dahir stone. The results of this study are in the form of a study of the Stuffelbeam and Dahir stone perspectives, namely the study of understanding, philosophy, and evaluation principles as a research basis related to the evaluation of guidance and counseling.